Inhibitory effects of Cinnamaldehyde, Carvacrol, and honey on the expression of exoS and ampC genes in multidrug-resistant Pseudomonas aeruginosa isolated from burn wound infections. (March 2020) - Mohammadzamani, Zahra; Khorshidi, Ahmad; Khaledi, Azad; Shakerimoghaddam, Ali; Moosavi, Gholam Abbas; Piroozmand, Ahmad
Abstract: This study aimed to evaluate the effects of Cinnamaldehyde, Carvacrol, and honey either alone or in combinations on the expression of exoS and ampC genes in multidrug-resistant (MDR) P. aeruginosa isolates. Thirty-five P. aeruginosa isolates were recovered from burn wound infections of patients admitted to the burn ward of Besat hospital of Hamadan, Iran, during 2018. Antibiotic susceptibility testing was performed using the Kirby-Bauer disk diffusion method to identify MDR isolates. The antibacterial effects of Cinnamaldehyde, Carvacrol, and honey either alone or in combinations with each other were compared to Imipenem (as the control group) using the broth dilution method. The expressions of exoS and ampC genes were determined in bacteria treated with sub-minimum inhibitory concentration (MIC) of the ternary combination of Cinnamaldehyde, Carvacrol, and honey by Real-Time-PCR. The data were analyzed using SPSS software applying student t-test, Kruskal-Wallis, and Mann-Whitney U tests. The P-value less than 0.05 was considered as statistically significant. The average MICs of Cinnamaldehyde, Carvacrol, and honey were 0.82–0.01, 0.01–0.6, and 62.5–250 μg/mL, respectively. The average MIC of the mentioned compounds was 430 times lower than that of Imipenem. A synergistic effect was detected between these drugs against 70% of the isolates. At sub-MIC concentration, the triple combination of Cinnamaldehyde, Carvacrol, and honey reduced the expressions of exoS and ampC genes by 6.12 and 2.85 folds, respectively. The combination of Cinnamaldehyde, Carvacrol, and honey showed a higher antibacterial effect than Imipenem. However, it needs confirmation with more isolates. Highlights: The average MIC of the mentioned compounds was 430 times lower than that of Imipenem. . A synergistic effect was detected between these compounds against 70% of the isolates. At sub-MIC concentration, the triple combination of Cinnamaldehyde, Carvacrol, and honey reduced the expressions of exoS and ampC genes by 6.12 and 2.85 folds, respectively.